"There is a God or There is No God—It is in the Hands of God": Fatalistic Beliefs Among Israeli People About Cancer and Their Impact on Behavioral Outcomes - Rosenfeld, Michal (Journal of religion and health, 2023)
This qualitative study examined fatalistic beliefs and cancer causal attributions among people without cancer. Participants were 30 Israeli women and men aged 51-70 from diverse sociocultural backgrounds who participated in four focus groups. Three main themes emerged, referring to the variability in fatalistic beliefs of cancer occurrence and cancer outcome, the duality in attributing causality to divine providence and mere luck or chance, and the connection between distinct fatalistic beliefs and health behaviors. Data analysis enabled an expansion of the understanding of cancer fatalism as a multidimensional structure, whereby interactions between causality attribution and different fatalistic beliefs are related to prevention and screening behaviors.